2019
DOI: 10.1002/adfm.201903487
|View full text |Cite
|
Sign up to set email alerts
|

Paper‐Based Electrochromic Devices Enabled by Nanocellulose‐Coated Substrates

Abstract: As environmental considerations for both the processing and disposal of electronic devices become increasingly important, the ability to replace plastic and glass substrates with bioderived and biodegradable materials remains a major technological goal. Here, the use of cellulose nanofiber-coated paper is explored as an environmentally benign substrate for preparing low-resistance (460 Ω sq −1 ), colorless (a* = −2.3, b* = −2.7) printed poly-(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 62 publications
1
61
1
Order By: Relevance
“…This mixed ion-electron conductor owes its success to a high electrical conductivity, spanning over several orders of magnitude and reaching values >1000 S cm −1 , an excellent ambient stability, and commercial availability as aqueous dispersions for processing via traditional coating and printing techniques 6 . Today, PEDOT: PSS has been employed as the charge extraction/injection layer in organic solar cells 7,8 and light-emitting diodes 9,10 , as well as the active material in electrochromic displays 11,12 , actuators 13,14 , electrochemical transistors [15][16][17] , sensors 18,19 , supercapacitors 20,21 , stretchable electronics 22,23 , thermoelectrics [24][25][26] , and brain-inspired memories 27,28 . However, many opto-and bioelectronic devices and systems rely on the complementarity of both high-performance hole-transporting and electron-transporting (n-type) materials.…”
mentioning
confidence: 99%
“…This mixed ion-electron conductor owes its success to a high electrical conductivity, spanning over several orders of magnitude and reaching values >1000 S cm −1 , an excellent ambient stability, and commercial availability as aqueous dispersions for processing via traditional coating and printing techniques 6 . Today, PEDOT: PSS has been employed as the charge extraction/injection layer in organic solar cells 7,8 and light-emitting diodes 9,10 , as well as the active material in electrochromic displays 11,12 , actuators 13,14 , electrochemical transistors [15][16][17] , sensors 18,19 , supercapacitors 20,21 , stretchable electronics 22,23 , thermoelectrics [24][25][26] , and brain-inspired memories 27,28 . However, many opto-and bioelectronic devices and systems rely on the complementarity of both high-performance hole-transporting and electron-transporting (n-type) materials.…”
mentioning
confidence: 99%
“…While an inorganic mixed conductor can be crystalline, the organic mixed conductors reported to date are typically amorphous, [ 29 ] and very little has been done for the characterization of their thermoelectric properties. The polymer blend composed of PEDOT as the hole conductor and PSS as the cation conductor is a typical mixed conductor used in many electrochemical devices, such as electrochromic displays, [ 30 ] supercapacitors, [ 31 ] and transistors. [ 32 ] PEDOT:PSS possesses an ionic conductivity of 0.03 S cm −1 at 80% RH, which is one order of magnitude lower than the electronic conductivity (0.3 S cm −1 at 80% RH).…”
Section: Figurementioning
confidence: 99%
“…Other studies also reported the switch behavior of paper EC devices. Lang et al [30] demonstrated EC devices with paper-based substrates and printed poly-(3,4ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) electrodes showing slower switching time when produced with a lateral device architecture. Tehrani et al [32] reported PEDOT:PSS-based EC displays with an extra layer of dihexyl-substituted poly(3,4-propylenedioxythiophene) (PProDOT-Hx2) and using flexible paper substrates in roll-to-roll printing.…”
Section: Electrochromic and Electrochemical Behaviormentioning
confidence: 99%
“…The EC materials are largely integrated in smart windows, displays and mirrors, however the demand for flexible devices has been gradually growing in the recent years, especially due to their conformability characteristic to unlike surfaces and the need to reduce production costs [29]. In this sense, electronics on paper appears as an attractive option as cellulose is the most abundant biopolymer on earth, inexpensive and guarantee highly flexibility to the device, despite being environmentally friendly [30]. In fact, paper has been included in several optoelectronic devices, including solar cells, transistors, among others [30,31], and lately paper started to appear as a reliable alternative for EC devices, as previously reported in [30,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%